Editorial JE-Unisla Vol 5 No 2 September 2020 - Zainal Abidin (Jurnal JE-UNISLA : Electronic Control, Telecomunication, Computer Information and Power System, 2020)
Editorial, Kata Pengantar dan Daftar Isi